Self-intensified synergy of a versatile biomimetic nanozyme and doxorubicin on electrospun fibers to inhibit postsurgical tumor recurrence and metastasis. (February 2023) - Hu, Yongwei; Xu, Yanteng; Mintz, Rachel L.; Luo, Xing; Fang, Youqiang; Lao, Yeh-Hsing; Chan, Hon Fai; Li, Kai; Lv, Shixian; Chen, Guojun; Tao, Yu; Luo, Yun; et al.
Abstract: Tumor-positive resection margins after surgery can result in tumor recurrence and metastasis. Although adjuvant postoperative radiotherapy and chemotherapy have been adopted in clinical practice, they lack efficacy and result in unavoidable side effects. Herein, a self-intensified in-situ therapy approach using electrospun fibers loaded with a biomimetic nanozyme and doxorubicin (DOX) is developed. The fabricated PEG-coated zeolite imidazole framework-67 (PZIF67) is demonstrated as a versatile nanozyme triggering reactions in cancer cells based on endogenous H2 O2 and O2 − . The PZIF67-generated OH induces reactive oxygen species (ROS) overload, implementing chemodynamic therapy (CDT). The O2 produced by PZIF67 inhibits the expression of hypoxia-up-regulated proteins, thereby suppressing tumor progression. PZIF67 also catalyzes the degradation of glutathione, further disturbing the intracellular redox homeostasis and enhancing CDT. Furthermore, the introduced DOX not only kills cancer cells individually, but also replenishes the continuously consumed substrates for PZIF67-catalyzed reactions. The PZIF67-weakened drug resistance strengthens the cytotoxicity of DOX. The combined application of PZIF67 and DOX also suppresses metastasis-associated genes. Both in vitro and in vivo results demonstrate that the self-intensified synergy of PZIF67 and DOX on electrospun fibers efficiently prevents postsurgical tumor recurrence and metastasis, offering a feasible therapeutic regimen for operable malignant tumors.